Pengaruh Kualitas Produk dan Citra Merek Terhadap Minat Beli Sepeda Motor Honda pada Masyarakat Karawang di Tengah Isu Rangka ESAF - Thoriq Baihaqi Al Syukri; Rieke Retnosary; Dini Yani (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2025)
The Indonesian automotive industry, particularly motorcycles, continue stogrowrapidly. However, qualityissues with the eSAF frame on several Honda motorcycle models have raised public concerns, affecting brand image and consumer purchaseintentions.This study aimsto analyze the impac tof productquality dan brand imageon consumer purchase intentions in Karawang, one of Honda's key markets, with a focus on the eSAF frame issue. A quantitative method was employed, with data collected through online Likert-scale-based questionnaires distributed to Karawang residents who have seenHonda promotions,areinterested in purchasing,orhave used Honda products. Using purposive sampling, the sample size was determined based on Structural Equation Modeling (SEM) recommendations. Data analysis was conducted using SEM-PLS to assess the relationships between product quality, brandimage, dan purchaseintentions. The findings are expected toprovide insights into the effect sof quality issue son consumer decisions dan offerstrategic recommendations formaintaining Honda’s positive brand image.